Fundamentals of thermodynamics - Sonntag, Richard E. (Wiley, 1998)
For the past three decades, Sonntag, Borgnakke, and Van Wylen's FUNDAMENTALS OF THERMODYNAMICS has been the leading textbook in the field. Now updated and enhanced with numerous worked examples, homework problems, and illustrations, and a rich selection of Web-based learning resources, the new Sixth Edition continues to present a comprehensive and rigorous treatment of classical thermodynamics, while retaining an engineering perspective. The text lays the groundwork for subsequent studies in fields such as fluid mechanics, heat transfer and statistical thermodynamics, and prepares students to effectively apply thermodynamics in the practice of engineering.